Anemia and its determinants among women of reproductive age of a slum in Kolkata: A focus group discussion among health workers in a slum of Kolkata - Dasgupta, Aparajita (J Family Med Prim Care, 2016)
CONTEXT: Anemia is a major contributor to morbidity and mortality among women of reproductive age. Progress toward reducing the burden of anemia has been little despite efforts through decades. AIMS: We conducted this study to unearth the microlevel determinants of anemia among women of reproductive age. SETTINGS AND DESIGN: This qualitative study was conducted in Urban Health Centre (UHC), Chetla. SUBJECTS AND METHODS: A focus group discussion was held among all the eight health staffs, who were involved in reproductive and child health-related service delivery under UHC, Chetla. ANALYSIS USED: A thematic analysis of the transcript was performed. RESULTS: We found that socioeconomic factors like poverty and social neglect, diet and nutrition related factors, lack of personal hygiene, and worm infestation contributed to the burden of anemia, and this was reinforced by factors related to service delivery, such as lack of supply of drugs and supplements, and inadequate training of health workers as well as poor media accountability. CONCLUSIONS: Because of easy reversibility and implementation, health service delivery-related issues should be addressed closely through monitoring and evaluation and appropriate and timely action should be taken to improve the effectiveness of the services.